Replika . miesięcznik niezależny Dolny Śląsk, no. 37, 1985 - Norwid, Cyprian, Kamil; Konarski, Feliks; Wałęsa, Lech; Falicki, Paweł (Agencja Wydawnicza Solidarności Walczącej, 1985)
Print run: 1200-2000 copies